If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11m + -3 = 3m + 2 Reorder the terms: -3 + 11m = 3m + 2 Reorder the terms: -3 + 11m = 2 + 3m Solving -3 + 11m = 2 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. -3 + 11m + -3m = 2 + 3m + -3m Combine like terms: 11m + -3m = 8m -3 + 8m = 2 + 3m + -3m Combine like terms: 3m + -3m = 0 -3 + 8m = 2 + 0 -3 + 8m = 2 Add '3' to each side of the equation. -3 + 3 + 8m = 2 + 3 Combine like terms: -3 + 3 = 0 0 + 8m = 2 + 3 8m = 2 + 3 Combine like terms: 2 + 3 = 5 8m = 5 Divide each side by '8'. m = 0.625 Simplifying m = 0.625
| x*x*(x+3)=200 | | 2(x+1)+2=3x-5 | | 2x+15=15x+32 | | X-2cosx=0 | | 3h+15=-6 | | 4w+4=2w+22 | | 17=3/2x | | x+2x-8=10 | | h+12=-24 | | 24x+2y=300 | | (3x/4-x/3-6=12)12 | | -3d=6.3 | | -2x-8=-6x+8 | | 4p=-3q | | 2z-30=180-x | | -9q=37 | | 68+30+5y-8=180 | | 68+30+5y-8=180 | | 7-(-8+4p)-3p=-6 | | 7−2/3xx−8 | | 15-20i/5i | | 16y-2=7x+3 | | 22-6a=8a-20 | | 3z+8y=5 | | 4x-22=-x-7 | | y-6=6y+14 | | (3x+10)+(5x+19)=180 | | 49m^2n^2+7mn-72=0 | | t(1)=-5(1)+29 | | 9=.416667x+4 | | Z/5=_-3 | | (3)(x+4)+15=(12) |